PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM MELALUI PENINGKATAN KUALITAS MANAJEMEN PENDIDIKAN - Alfisyah; Ahmad Naufal; Raisha Khotimah; Suriagiri; Muhammad Nur Effendi (PT. Hasba Edukasi Mandiri, 2026)
Islamic educational institutions in Indonesia face serious systemic challenges in institutional governance that impede quality improvement and competitiveness in an era of accelerating globalisation. This study aims to analyse the urgency and role of educational management in the development of Islamic educational institutions, to identify effective strategies for improving management quality, and to describe the role of evaluation and innovation in strengthening institutional sustainability. A qualitative approach was employed through a library research method of a conceptual and descriptive-analytical nature. Data sources comprised peer-reviewed journals, educational management texts, and relevant research reports, which were examined using content analysis and qualitative-descriptive analysis techniques. The findings reveal that the management of most Islamic educational institutions remains dominated by traditional, top-down leadership patterns, is weak in strategic planning, and makes minimal use of management technology; these conditions collectively suppress service quality and institutional competitiveness. Three interdependent factors were consistently identified as the primary determinants of sustainable institutional development: the quality of management and the availability of professional human resources, community support and public trust, and the existence of a functioning system of evaluation and continuous innovation. This study concludes that high-quality educational management, namely one that integrates the POAC functions (Planning, Organising, Actuating, Controlling), Total Quality Management (TQM) principles, strategic management approaches, and core Islamic managerial values such as amanah, syura, and itqan, constitutes the cornerstone for developing Islamic educational institutions that are excellent, adaptive, and highly competitive in meeting the educational challenges of the twenty-first century.